Cordylobia rodhaini infestation of the breast: Report of a case mimicking a breast abscess. (2016) - Grassi, Veronica; Butterworth, James William; Latiffi, Layloma
Abstract: Introduction: Myiasis, parasitic infestation of the body by fly larvae, caused by the Cordylobia rodhaini is very rare with only fourteen cases published since 1970. We present a rare case of myiasis mimicking a breast abscess. Presentation of case: A 17-year-old female presented with a nodular ulcerative lesion in her left breast 14 days following a trip to Ghana. She had been initially unsuccessfully treated with the antibiotic flucloxacillin following a misdiagnosis of a breast abscess. Following application of Vaseline to the breast wound, covering the wound for 2 h and gentle manipulation the larvae was removed successfully and the patient made a good recovery. Discussion: Presenting as an inflammatory papule with central opening oozing serosanguinous fluid myiasis secondary to C. rodhaini can easily be mistaken for a breast abscess, often avoiding detection by unsuspecting surgeons on initial assessment. In turn ineffective antibiotic treatment is often prescribed leading to further disease progression and associated morbidity. Conclusion: Myiasis secondary to C. rodhaini is a rare but important differential surgeons should consider in women presenting with an inflammatory breast lesion with a recent history of foreign travel to ensure timely diagnosis and treatment. Ultrasound imaging can be useful in confirming diagnosis and avoiding treatment delays.